1-Triacontanol cerotate; isolated from Marsilea quadrifolia Linn. ameliorates reactive oxidative damage in the frontal cortex and hippocampus of chronic epileptic rats. (22nd August 2015) - Snehunsu, Adhikari; Ghosal, Chitrini; Kandwal, Mamta; Yadav, Pramod K.; Nayak, B. Satheesha; Rao, K. Raghavendra; Kamath, Shobha U.; Sahoo, Pabitra; Srinivasan, K.K.; Naduvil Narayanan, Sareesh; Kumar, Shiva; Joseph, Alex
Abstract: Ethnopharmacological relevance: Marsilea quadrifolia Linn. (MQ) has been used for insomnia and epileptic disorders in traditional Indian medicine. The present study is to isolate the active component responsible for antiepileptic property of MQ by evaluating its ability to minimize the reactive oxidative damage in brain due to chronic epilepsy in rat. Materials and methods: 1-Triacontanol cerotate (1TAC) was isolated after chromatography on a silica gel from dried petroleum ether fraction of methanolic extract of MQ. Acute oral toxicity studies of 1TAC were carried out and efficacy of 1TAC on malondialdehyde (MDA) and reduced glutathione (GSH) production in different brain areas of chronic pentylenetetrazole (PTZ) induced epileptic rats were evaluated. Results: Our results showed that PTZ-kindled chronic epileptic rats had an increase MDA and decreased GSH concentration in the frontal cortex as well as hippocampus, compared to the normal control. MDA and GSH concentrations in those brain areas were normalized after treatment with sodium valproate (SV) in 200 mg kg −1  bw; as well as 1TAC in 40 and 80 mg kg −1  bw doses. Conclusion: Production of reactive oxygen species( ROS) is known to worsen epileptogenesis. The isolated component 1TAC which reduced the reactive oxidative damage in hippocampus and frontal cortex of PTZ kindled rats could be responsible for antiepileptic property of MQ. Its action is found to be dose dependent, with 80 mg kg −1  bw showing even better efficacy than 200 mg kg −1  bw of SV. Graphical abstract: